Occurrence of Cylindrocarpon spp. in Nursery Grapevines in California - Dubrovsky, S.; Fabritius, A.L. (Phytopathologia Mediterranea, 2007)
Cylindrocarpon liriodendri and C. macrodidymum are causal agents of black foot disease of grapevines in California. Together with Phaeoacremonium spp. and Phaeomoniella chlamydospora, Cylindrocarpon spp. are also known to be associated with decline of young vines. Infected vineyard soils are one source of the Cylindrocarpon infections, but nurseries have also been shown to contribute to the origin of the inoculum. To study incidence of Cylindrocarpon spp. in nursery grapevines in California, randomly selected, non-symptomatic grapevines from various nurseries were tested in a PCR assay for the presence of Cylindrocarpon spp. Results of this study suggested that Cylindrocarpon spp. are the most common pathogens associated with young nursery vines in California, being detected in 26% of the samples. Phaeoacremonium aleophilum was found in 19% and P. chlamydospora in 4% of the nursery samples.